f(x) = (x^2 + 3x -2)^2

Let us calculate f'(x)

f'(x) = 2(x^2 + 3x -2) *(2x + 3)

= (2x^2 + 6x -4 )(2x + 3)

f'(1) = (2 + 6 -4)(2 +3)

= 4*5 = 20

==> f'(1) = 20

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now